A visual editing tool supporting the production of 3D interactive graphics assets for public exhibitions. Issue 141 (September 2020) - Cannavò, Alberto; Pace, Francesco De; Salaroglio, Federico; Lamberti, Fabrizio
Highlights: Interactive applications can enhance the users experience in public exhibitions. Visual languages offer intuitive ways to easily create interactive applications . Tool letting users with no programming skills create interactive 3D applications. Results showed higher effectiveness and appreciation w.r.t. previous alternatives. Abstract: The introduction of interactive assets in public exhibitions is capable to significantly enhance the visitors' user experience. However, the creation of interactive applications could represent a challenging task, especially for users lacking computer skills. Visual programming languages (VPLs) – one of the instruments belonging to the broad categories of methods and tools devised to support end-user development (EUD) – promise to offer an intuitive way to overcome these limitations, by providing easy-to-use and efficient interfaces for encoding applications' logic. Moving from these considerations, this paper first analyses pros and cons of tools devised so far to support the generation of interactive contents. Then, it presents the design of a new tool named Visual Scene Editor (VSE), which allows users with little to no programming skills to create 3D interactive applications by combining available assets through an interactive, visual process. Both objective and subjective measurements have been collected with both skilled and unskilled users to evaluate the performance of the proposed tool. A comparison with existing solutions shows a reduction in the time required to complete the assigned tasks, of the complexity of the logic created, as well as of the number of errors made, confirming the suitability of the VSE for the said purpose.